Doppler‐derived renal resistive index helps predict acute kidney injury in patients undergoing living‐related liver transplantation. Issue 5 (4th March 2021) - Shankar, Vijay; Raj, Anupam; Singhal, Saurabh; Sahni, Reeti; Goyal, Neerav; Venuthurimilli, Arun; Olson, Michael T.; Chatterji, Chitra
Abstract: Background: Acute kidney injury (AKI) is commonly associated with increased postoperative morbidity in liver transplant (LT) recipients. The aim of this study was to identify the role of renal resistive index (RRI) in predicting AKI and to study the factors associated with AKI in LT recipients. Patients and methods: We performed a single‐center, prospective study, including adult living donor LT recipients at our center between January 2018 and September 2019 with no preoperative renal dysfunction. RRI was calculated on ultrasound doppler once preoperatively, and once daily in the postoperative period through postoperative day (POD) six. Patients were grouped into AKI and non‐AKI groups for comparison. Results: Fifty patients were included in the study (mean age, 44 years; 20% females). AKI developed in 25 patients (50%). Both groups were similar in baseline characteristics. RRI of ≥ 0.69 on POD 2 predicted AKI (sensitivity 88%; specificity 92%). RRI on the day before AKI diagnosis (0.71 vs. 0.65) and on the day of diagnosis (0.72 vs. 0.65) were significantly increased relative to preoperative baseline. Conclusions: Doppler‐derived RRI is a rapid, non‐invasive, and bedside procedure capable of predicting the occurrence of postoperative AKI in LT recipients.